Aging Back Clinics—a Geriatric Syndrome Approach to Treating Chronic Low Back Pain in Older Adults: Results of a Preliminary Randomized Controlled Trial. Issue 2 (10th September 2019) - Weiner, Debra K; Gentili, Angela; Rossi, Michelle; Coffey-Vega, Katherine; Rodriguez, Keri L; Hruska, Kristina L; Hausmann, Leslie; Perera, Subashan
Abstract: Objective: Treating chronic low back pain (CLBP) with spine-focused interventions is common, potentially dangerous, and often ineffective. This preliminary trial tests the feasibility and efficacy of caring for CLBP in older adults as a geriatric syndrome in Aging Back Clinics (ABC). Design: Randomized controlled trial. Setting: Outpatient clinics of two VA Medical Centers. Subjects: Fifty-five English-speaking veterans aged 60–89 with CLBP and no red flags for serious underlying illness, prior back surgery, dementia, impaired communication, or uncontrolled psychiatric illness. Methods: Participants were randomized to ABC care or usual care (UC) and followed for six months. ABC care included 1) a structured history and physical examination to identify pain contributors, 2) structured participant education, 3) collaborative decision-making, and 4) care guided by condition-specific algorithms. Primary outcomes were low back pain severity (0–10 current and seven-day average/worst pain) and pain-related disability (Roland Morris). Secondary outcomes included the SF-12 and health care utilization. Results: ABC participants experienced significantly greater reduction in seven-day average (–1.22 points, P = 0.023) and worst pain (–1.70 points, P = 0.003) and SF-12 interference with social activities (50.0 vs 11.5%, P = 0.0030) at six months. ABC participants were less likely to take muscle relaxants (16.7 vs 42.3%, P = 0.0481). Descriptively, UC participants were more likely to experience pain-related emergency room visits (45.8% vs 30.8%) and to be exposed to non-COX2 nonsteroidal anti-inflammatory drugs (73.1% vs 54.2%). Conclusions: These preliminary data suggest that ABC care for older veterans with CLBP is feasible and may reduce pain and exposure to other potential morbidity.